Not a Cheap Investment: Estimating the Cost of the 2017 to 2018 Ophthalmology Residency Match to the Applicant and Program - Moore, Daniel B. (Journal of Academic Ophthalmology, 2018)
Purpose To estimate the cost of the match process for all ophthalmology applicants and the departmental costs at the University of Kentucky during the 2017 to 2018 match cycle.Design Financial analysis.Methods Using the available national match statistics for the 2017 to 2018 ophthalmology residency match and the mean of all residency interview costs available in the literature, the estimated mean and total match costs were calculated for all applicants, including application fees and interviews. Program costs were estimated based on direct interview costs, lost productivity, and fixed costs.Results Of 625 applicants, 475 matched into an ophthalmology residency position in 2017 to 2018. The mean estimated cost was US$6,613 for matched applicants, and all applicants spent US$4,646,950 on the match in aggregate. Our department spent an estimated US$179,327 over four interview days with 12 faculty volunteers, or an average of US$3,736 per each of 48 interviewed applicants.Conclusions and Relevance Matching into an ophthalmology residency position is expensive not only for the applicant but also the program. Reforms to the process would likely be beneficial to both parties.
Keywords: ophthalmology; residency match; residency interviews; residency application; cost; medical student